Digitalization in Candidate Selection. Support and Resistance Within Established Political Parties in Germany - Claire Bloquet; Isabelle Borucki; Benjamin Höhne; Benjamin Höhne (Frontiers in Political Science, 2022)
The digitalization of human life has impacted many aspects of politics in the last two decades. Intra-party decision-making is one of them. While new political parties appear to be rather native digital organizations, established parties are increasingly beginning to incorporate online tools into their internal processes. However, not much is known about how intra-party selectorates evaluate the digitalization of a crucial decision-making process. This study asks whether party members who participate in candidate selection support online consultations—or not. Using an original large-N dataset on the preferences of party members attending candidate selection assemblies for the German Bundestag, we determine variables that increase or decrease the likelihood to support the introduction of online consultations as part of intra-party democracy. Our results show that attitudes toward digitalization do not depend on a generational or a partisan factor, as might have been expected. Instead, we highlight that digitalization support is first and foremost related to, on the one hand, the seniority in the party, and, on the other, on one's preferences toward inclusion. We relate these findings to the distribution of powers and incentives within the party and discuss both the implications of these results and what they might mean for established parties trying to reform.